2009
DOI: 10.1007/s12540-009-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Grain structure and texture evolutions during single crystal casting of the Ni-base superalloy CMSX-4

Abstract: The solidification grain structure and texture evolutions during single crystal (SX) casting of the advanced Ni-base superalloy CMSX-4 have been investigated. In order to understand the development of the solidification grain structure, SX casting experiments were carried out with a specially designed grain selector in a Bridgman directional solidification (DS) furnace. In addition to casting trials, the SX casting process was simulated by a 3-D cellular automaton-finite element (CAFE) model. The predicted sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…Note that the DSC exothermic peak at 1402 K could not be observed in the DSC curve of the alloy CM247LC, whose as-cast microstructure is composed of primary c, MC carbide, c/c¢ eutectic, and c¢ precipitates. [14] However, because the onset temperatures of MC carbide, c/c¢ eutectic, c¢ precipitation, and eta and boride phases were concealed by the trail of primary c solidification peak, the exact phase transformation temperature of these phases could not be determined by the DSC analysis. Nevertheless, assuming that the formation of eta and boride phases continues below their peak temperature (1402 K), the solidification range, which is defined as the temperature difference between the primary c formation and the end of solidification, might be about 196 K.…”
Section: Solidification Sequence Of Eta and Boride Phasesmentioning
confidence: 99%
“…Note that the DSC exothermic peak at 1402 K could not be observed in the DSC curve of the alloy CM247LC, whose as-cast microstructure is composed of primary c, MC carbide, c/c¢ eutectic, and c¢ precipitates. [14] However, because the onset temperatures of MC carbide, c/c¢ eutectic, c¢ precipitation, and eta and boride phases were concealed by the trail of primary c solidification peak, the exact phase transformation temperature of these phases could not be determined by the DSC analysis. Nevertheless, assuming that the formation of eta and boride phases continues below their peak temperature (1402 K), the solidification range, which is defined as the temperature difference between the primary c formation and the end of solidification, might be about 196 K.…”
Section: Solidification Sequence Of Eta and Boride Phasesmentioning
confidence: 99%
“…However, the relative growth directions significantly influence the competitive growth of grains. It was found that grains with larger misorientations were preserved on top of the starter block for improper geometry design [18,19], meaning that unfavorable grains were not overgrown through a long competitive growth distance. This illustrated that the misaligned grains would have great growth advantage and can overgrow the well-aligned grains under special conditions.…”
Section: Grain Competitive Growth Mechanismmentioning
confidence: 99%
“…The mechanism of grain selection during directional solidification and the opting of one grain from a set of columnar grains have been studied by various researchers both experimentally and theoretically . Initially, Schneider et al.…”
Section: Introductionmentioning
confidence: 99%